Lysine Demethylase KDM6A in Differentiation, Development, and Cancer - Tran, Nhien (Mol Cell Biol, 2020)
Lysine demethylase 6A (KDM6A), also known as UTX, belongs to the KDM6 family of histone H3 lysine 27 (H3K27) demethylases, which also includes UTY and KDM6B (JMJD3). The KDM6A protein contains six tetratricopeptide repeat (TPR) domains and an enzymatic Jumonji C (JmjC) domain that catalyzes the removal of di- and trimethylation on H3K27. KDM6A physically associates with histone H3 lysine 4 monomethyltransferases MLL3 (KMT2C) and MLL4 (KMT2D). Since its identification as an H3K27 demethylase in 2007, studies have reported KDM6A’s critical roles in cell differentiation, development, and cancer. KDM6A is important for differentiation of embryonic stem cells and development of various tissues. Mutations of KDM6A cause Kabuki syndrome. KDM6A is frequently mutated in cancers and functions as a tumor suppressor. KDM6A is redundant with UTY and functions largely independently of its demethylase activity. It regulates gene expression, likely through the associated transcription factors and MLL3/4 on enhancers. However, KDM6A enzymatic activity is required in certain cellular contexts. Functional redundancy between H3K27 demethylase activities of KDM6A and KDM6B in vivo has yet to be determined. Further understanding of KDM6A functions and working mechanisms will provide more insights into enhancer regulation and may help generate novel therapeutic approaches to treat KDM6A-related diseases.